The Effect of Moringa oleifera Flour Addition on The Quality of Chicken Meat Dimsum - Yuliana Risma Wulandari; Afifah Novidia Nurhassarah; Lilik Eka Radiati (Jurnal Ilmu dan Teknologi Hasil Ternak)
The effect of Maringa oleifera flour addition on protein, moisture content, ash, fat content, texture, water holding capacity, organoleptic and color L*, a*, b in chicken meat dimsum. The treatments used were without the addition of moringa flour as a control and the addition of moringa flour 1%, 2%, and 3%. The variables measured were protein, moisture content, ash, fat content, texture, water holding capacity, organoleptic and color L*, a*, b*. The results showed that the treatment gave a significant effect (p < 0.05) on protein, moisture content and water holding capacity, gave a highly significant effect (p < 0.01) on ash content, organoleptic color, aroma, and taste, gave no significant effect (p > 0.05) on fat content, texture and texture organoleptic. The results of color testing L*, a*, b* has a highly significant effect (p < 0.01) on brightness (L*), a significant effect (p < 0.05) on redness (a*) and no significant effect (p > 0.05) on yellowness (b*). It can be concluded that the addition of moringa leaf flour at 3% in chicken meat dimsum gives the best results in terms of protein content of 13.45%, moisture content of 60,20%, ash content of 1,53%, fat content of 1,66%, texture of 5.15 N, water holding capacity 31%, organoleptic values of color 1.4, aroma 1.56, taste 2.05, and texture 3.1 and color lightness (L*) 54,25%, redness (a*) 0,97%, and yellowness (b*) 17,62%. The research suggestion is to use moringa leaf flour at 3% for good result in chemical qualities and use moringa leaf flour at 1% for good result in physical qualities.